INTEGRATING PRODUCTION SCHEDULING, DELIVERY, AND 3D LOADING PROBLEMS IN A TWO STAGE SUPPLY CHAIN - Keshavarz, Taha; Noormohamadzade, Zohreh; Fakhrzad, Mohammad Bagher (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
In this study, a two echelon supply chain with one distribution center and several retailers is investigated. In the distribution center, handling of retailer’s orders is considered as an operation that should be completed on a single workstation. This study combines production scheduling and delivery problems with three-dimensional (3D) loading problem. In the integration of production scheduling and delivery problems, production and inventory and transportation decisions are considered simultaneously in order to minimize the sum of production setup costs, inventory costs and routing costs. The purpose of this problem is to determine the sequence and quantity of production, type of vehicles, the visiting sequence of each vehicle, and the inventory level at the distribution center and retailers, so that the total cost is minimized. The total cost includes the production setup costs, holding cost in the distribution center, transportation cost, vehicle arrangement cost and penalty costs. Then, the vehicles and batches are considered as 3D components with length, width and height and the 3D loading problem is investigated. The purpose of 3D loading problem is to provide a practical loading. A mathematical model is presented to solve the loading problem. The problem under study is NP-hard, so medium and large sized instances cannot be solved optimally in a reasonable time. Hence, a meta-heuristic algorithm based on genetic algorithm is proposed to solve the problem. The computational results show that the proposed algorithm decreases the computational times 85.29% in average and only leads to 3.22% increase in the total cost in comparison with the optimal solution.